Emotional intelligence as a predictor of clinical competence in nursing students - Maryam Aghabarary; Mahsa Khedmatizare (BMC Research Notes)
Abstract Background Clinical competence and emotional intelligence are both essential factors for the success of nursing students in their profession. Due to the inconsistent findings regarding the relationship between clinical competence and emotional intelligence in nursing students, this study aims to investigate this relationship among nursing students at Alborz University of Medical Sciences, Iran. Methods In this descriptive, correlational, cross-sectional study, 220 nursing students from the 2nd to the 8th semester were included in the study by census method. The data were collected using a questionnaire comprising three sections: demographic information, clinical competence assessment, and emotional intelligence assessment. Data analysis was performed using descriptive and inferential statistics with SPSS software version 22, at a significance level of P ≤ 0.05. Results Out of 220 nursing students, 176 completed the questionnaires. The mean score of participants’ clinical competence was 102.58 ± 19.94, indicating a moderate level. The emotional intelligence of the students also showed a moderate level, with a mean score of 81.16 ± 7.04. A significant positive correlation was observed between clinical competence and emotional intelligence (P < 0.001). The predictive role of three dimensions of emotional intelligence (self-awareness, self-management, and relationship management) was confirmed (P < 0.05). Conclusion In this study, a positive and significant correlation was observed between clinical competence and emotional intelligence, indicating that higher emotional intelligence is associated with greater clinical competence. Accordingly, it is recommended to design and implement interventional studies aimed at enhancing students’ emotional intelligence and evaluating the effectiveness of such interventions on their emotional intelligence and clinical competence.